178k views
4 votes
Solve for x: -3(x + 1)= -3(x + 1) - 5

1 Answer

3 votes

Answer:

No solution : 0= -5

Explanation:


-3\left(x+1\right)=-3\left(x+1\right)-5\\\\\mathrm{Add\:}3\left(x+1\right)\mathrm{\:to\:both\:sides}\\\\-3\left(x+1\right)+3\left(x+1\right)=-3\left(x+1\right)-5+3\left(x+1\right)\\\\\mathrm{Simplify}\\\\0=-5\\\\\mathrm{The\:sides\:are\:not\:equal}\\\\\mathrm{No\:Solution}

User Parsethis
by
5.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.